ANALISIS KONSEPTUAL MODEL PEMBELAJARAN TGT DALAM PERSPEKTIF PENDIDIKAN ISLAM - Amia Kasmila; Imam Syafe’I; A’La Nirotul Fikri; A’vi Amelia; Diah Irdiyana Rizqi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to examine the Teams Games Tournament (TGT) learning model from the perspective of Islamic education and its relevance to Islamic Religious Education (IRE) learning. The research employed a qualitative method using a library research approach. Data were collected through an extensive review of scholarly sources, including books, journal articles, and other relevant literature concerning cooperative learning and Islamic educational values. The findings indicate that the TGT model is highly suitable for implementation in IRE learning because it encourages active student participation, strengthens collaborative skills, enhances learning motivation, and contributes to improved academic achievement. Furthermore, the core principles embedded in the TGT model are consistent with Islamic teachings, particularly the values of ta’awun (mutual assistance), ukhuwah (brotherhood), and fastabiqul khairat (competing in doing good deeds). Through group-based activities, educational games, academic tournaments, and reward systems, the learning process becomes more engaging, interactive, and enjoyable for students. Therefore, the TGT model can serve as an effective instructional strategy for improving the quality of Islamic Religious Education while simultaneously fostering positive character development and healthy competitiveness among learners. ABSTRAK Penelitian ini bertujuan untuk mengkaji model pembelajaran Teams Games Tournament (TGT) dalam perspektif pendidikan Islam serta relevansinya terhadap pembelajaran Pendidikan Agama Islam (PAI). Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kepustakaan (library research). Data diperoleh melalui penelaahan berbagai sumber ilmiah, seperti buku, artikel jurnal, dan literatur yang berkaitan dengan pembelajaran kooperatif serta nilai-nilai pendidikan Islam. Hasil kajian menunjukkan bahwa model TGT memiliki potensi yang besar untuk diterapkan dalam pembelajaran PAI karena mampu meningkatkan partisipasi aktif siswa, memperkuat kerja sama antarpeserta didik, menumbuhkan motivasi belajar, serta mendukung peningkatan hasil belajar. Selain itu, prinsip-prinsip yang terkandung dalam model TGT selaras dengan ajaran Islam, khususnya nilai ta’awun (tolong-menolong), ukhuwah (persaudaraan), dan fastabiqul khairat (berlomba-lomba dalam kebaikan). Implementasi kegiatan kelompok, permainan edukatif, turnamen akademik, dan pemberian penghargaan menjadikan proses pembelajaran lebih menarik, interaktif, dan menyenangkan. Dengan demikian, model TGT dapat menjadi salah satu alternatif strategi pembelajaran yang efektif untuk meningkatkan kualitas pembelajaran PAI sekaligus membentuk karakter peserta didik yang berakhlak dan kompetitif secara positif.